M cells targeted H. pylori antigen SAM-FAdE displayed on bacterium-like particles induce protective immunity - Furui Zhang; Jiale Chen; Zhen Zhang; Jing Wu; Yuliang Qu; Linhan Ni; Guolin Zhang; Kunmei Liu; Le Guo (Journal of Nanobiotechnology)
Abstract Background Helicobacter pylori (H. pylori), a specific bacterium capable of surviving in the acidic environment of the stomach, has been recognized as a group of causative agents of gastric cancer. Therefore, the development of mucosal vaccines against H. pylori is expected to provide an important direction for the treatment of chronic gastritis and the prevention of gastric cancer. Methods and results In this study, we used bacteria-like particles (BLPs) obtained by treating Lactic acid bacteria (L. lactis) with hot acid, and successfully displayed the M cell-targeted H. pylori multi-epitope purified antigen SAM-FAdE, with 90% display efficiency. In addition, BLPs-SAM-FAdE can effectively target M ​​cell models and M cells of mouse Peyer’s patches (PPs) through oral immunization, promote the transport of particulate vaccines to dendritic cells (BMDCs) and stimulate their maturation, significantly increased proportion of plasma cells and germinal centers B cells. This indicates that the vaccination can induce notable antigen-specific mucosal immune responses (production of sIgA), CD4+ T cell responses (Th1/Th2/Th17) and humoral immune responses (production of serum IgG). Furthermore, oral BLPs-SAM-FAdE dramatically reduced the H. pylori adhesion and specific 16S rRNA expression of H. pylori in gastric mucosal tissue, protecting gastric tissue from damage. Conclusion BLPs-SAM-FAdE can significantly reduce the adhesion of H. pylori in gastric mucosal tissue and inhibit gastritis and gastric damage caused by H. pylori infection.